Negotiating India's past : essays in memory of Partha Sarathi Gupta - Gupta, Partha Sarathi 1934-; Pati, Biswamoy; Sahu, B. P. 1957-; Venkatasubramanian, T. K. (New Delhi : Tulika Books, 2003)
Festschrift honoring Partha Sarathi Gupta, Indian historian; contributed articles on Indian historiography.
Ideology, legitimacy, and the state -- Of environment, exchange, and economic transactions -- Social change and resistance.
Includes bibliographical references and index.
Keywords: India -- Historiography